Insights to the 3D internal morphology and metal oxidation states of single atmospheric aerosol particles by synchrotron-based methodology. (November 2022) - Young, Li-Hao; Chen, Wan-Yi; Wang, Chun-Chieh; Tang, Mau-Tsu; Tseng, Shao-Chin; Lin, Bi-Hsuan; Lai, Chau-Wei; Chen, Yu-Han; Yang, Tzu-Ting; Lin, Yao-Tung
Abstract: The morphology and metal oxidation states of atmospheric aerosols are pertinent to their formation processes and ensuing interactions with surrounding gases, vapors and other environments upon deposition, such as human respiratory tract, soil and water. Although much progress has been made in recent years through single-particle techniques, considerably less is known with respect to the three-dimensional (3D) internal morphology of single atmospheric aerosol particles due to the limited penetration depth of electron microscopy. In this study, for the first time, a novel synchrotron-based transmission X-ray microscopy (TXM) methodology has been developed to visualize the 3D internal chemical mixing state and structure of single particles. The results show that the TXM is more applicable to the imaging of solid particles containing high-density elements, e.g., iron (Fe), aluminum (Al), silicone (Si), carbon (C) and sulfur (S), and/or solid particles of sizes larger than about 100 nm. In addition, the TXM is capable to reveal the fine 3D topographic features of single particles. The derived 3D internal and external information would be difficult to discern in the 2D images from electron microscopy. The TXM 3D images illustrate that aerosol particles exhibit complex internal mixing state and structure, e.g., homogeneously-, heterogeneously-mixed, multiple inclusions, fibrous, porous, and core-shell configuration. When coupled with the synchrotron-based X-ray fluorescence spectrometry (XRF) and absorption near-edge spectroscopy (XANES) of an X-ray nanoprobe in the energy range of 4–15 keV, the 3D morphology of single particles is further supplemented with the spatial distribution and oxidation sates of selected elements, including Fe, vanadium (V), manganese (Mn), chromium (Cr) and arsenic (As). The presented cross-platform, synchrotron-based methodology shows promise in complementing existing single-particle techniques and providing new insights to the heterogeneity of single-particle micro-physicochemical states relevant to the aerosol chemistry, optical properties, and their environmental and health impacts. Graphical abstract: The 3D external and internal morphology of a single core-shell particle and the metal oxidation state in a single particle. Image 1 Highlights: A synchrotron-based methodology was developed for single particle analysis. The method consisted of a transmission X-ray microscope and an X-ray nanoprobe. The external and internal morphology of single particles was visualized in 3D. Single particles exhibited complex internal chemical mixing state and structure. Metals were nonuniformly distributed and their oxidation sates were determined.